State-of-the Art and Development Prospects of Digital Radiography Systems for Nondestructive Testing, Evaluation, and Inspection of Objects: a Review; Russian Journal of Nondestructive Testing; Vol. 52, iss. 9 - Udod V. A. Viktor Anatolievich; Van Ya.; Osipov S. P. Sergey Pavlovich; Chakhlov S. V. Sergey Vladimirovich; Usachev E. Yu.; Lebedev M. B.; Temnik A. K. Anatoly Konstantinovich (2016, 2016)
Title screen